Effect of sucrose on actinorhodin production by Streptomyces coelicolor A3(2) - Elibol, M; Mavituna, F (Elsevier Sci Ltd, 1998)
The effect of sucrose on actinorhodin production by Streptomyces coelicolor was investigated using both defined and complex media. Both media contained glucose as the main carbon source and sucrose was included for osmotic balance. The production of antibiotic in the defined medium decreased with the addition of sucrose but, when sucrose was excluded from the complex medium, the culture did not produce actinorhodin. A sucrose concentration of 340 g/litre was optimal for actinorhodin production in the complex medium. (C) 1998 Elsevier Science Ltd.
Keywords: actinorhodin; antibiotic; osmotic pressure; Streptomyces coelicolor; sucrose